Pengaruh Pemberian Rebusan Jahe terhadap Penurunan Tekanan Darah pada Lansia Hipertensi di Wijaya Kusuma, Jakarta Barat - Gaung Eka Ramadhan; Aliffa Putri Surya Balqis; Tati Suryati (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
This study aims to determine the effect of giving ginger decoction to reducing blood pressure in elderly hypertensives. This study used a quasi-experimental design with a pre-post test without control group design. The population in this study were elderly people who suffer from hypertension in RT 07 Wijaya Kusuma, West Jakarta. The number of samples in this study were 22 people using the total sampling technique. The instruments in this study were 4gr ginger, 200cc water, digital scales, honey, knife, measuring cup, and digital tensimeter (automatic). The research results showed that the average systolic blood pressure at the first measurement (pre test) was 141.32 mmHg with a standard deviation of 10.242. In the last measurement (Post Test) the average systolic blood pressure was 132.59 mmHg with a standard deviation of 3.912 while the average diastolic blood pressure in the first measurement (Pre Test) was 94.27 mmHg with a standard deviation of 10.416 and in the last measurement (Post Test) was 81.55 mmHg with a standard deviation of 7.614. Statistical analysis using the paired t-test showed p value = 0.001 so it can be concluded that there is an effect of giving ginger decoction to reducing blood pressure in elderly hypertensives. Based on the results of the study, nurses are expected to be able to provide interventions to address hypertension problems by administering ginger decoction which can lower blood pressure on an ongoing basis without significant side effects and can be used as traditional medicine in patients with hypertension.